Preliminary phytochemical, Proximate and Nutrient Analysis indifferent leaf extracts of Jatropha curcas L - Vasthi Kennedy Evanjelene; Ganesh Velu (Indian Journal of Pharmacy & Drug Studies, 2023)
The current study looks at the phytochemical analysis, proximate composition, and nutrient content of different Jatropha curcas L. leaf extracts in-vitro. Preliminary phytochemical studies were also carried out to identify the classes of compounds found in different J. curcas leaf extracts. Proximate analysis (moisture, ash, total protein, fats, fibre, carbohydrate, and energy content) was done using the Association of Official Analytical Chemists' methods. Atomic absorption spectrometry was used to examine macronutrients (Ca, Mg, Na, K) and micronutrients (Fe, Cu, Pb, Zn, Ni, Cr, Cd). The results of the study revealed that J. curcas has a higher proximate and nutrient value, with a strong association between the two. J. curcas has also been discovered to be useful in medicine and food. In conclusion, the thesis demonstrated the biological potency of the plant and provided scientific support for its use in Indian medicine.